Predictors of children's and young people's digital engagement in informational, communication, and entertainment activities: findings from ten European countries. Issue 1 (2nd January 2023) - Cino, Davide; Lacko, David; Mascheroni, Giovanna; Šmahel, David
ABSTRACT: Through a re-analysis of survey data collected with a sample of 9, 731 youth aged 11–17 from 10 European countries, the article explores how some of the most popular online activities for children and young people (i.e., informational, social, and entertainment activities) relate to different types of perceived digital skills, as well as individual and social characteristics (such as age, gender, emotional problems, sensation seeking, parental mediation, and family environment). Furthermore, this paper looks at the moderating role of the family environment between enabling parental mediation and online activities. Using multi-group structural equation modeling we found that emotional problems, perceived informational and social digital skills, and enabling parental mediation were associated with informational online activities; sensation seeking, perceived informational digital skills, and enabling and restrictive parental mediation were associated with social online activities; and restrictive parental mediation was associated with entertainment online activities. Implications of these findings for educators, policy-makers, and parents are outlined, as well as limitations and future directions. Impact summary: Prior State of Knowledge : When going online, children and young people more commonly engage in informational, communication, and social activities. While different online activities may promote different positive outcomes, variables like digital skills, individual and social characteristics make a difference in what they do. Novel Contributions : We found that perceived informational digital skills was the most consistent predictor of all kinds of online activities, followed by enabling parental mediation positively predicting engagement in informational and social activities and restrictive mediation negatively predicting social and entertainment activities. Practical Implications : Findings are informative for policy-makers and educators to promote curricula fostering informational digital skills, predicting engagement in all kinds of activities, and parents to adopt an enabling mediation style allowing children to undertake a more diverse range of online activities.